Membrane Compartmentalization and Scaffold Proteins in Leukocyte Migration - Samson, Guerric P. B.; Legler, Daniel F. (Frontiers in Cell and Developmental Biology, 2020)
Leukocyte migration across vessels into and within peripheral and lymphoid tissues is essential for host defense against invading pathogens. Leukocytes are specialized in sensing a variety of guidance cues and to integrate environmental stimuli to navigate in a timely and spatially controlled manner. These extracellular signals must be transmitted across the leukocyte’s plasma membrane in a way that intracellular signaling cascades enable directional cell movement. Therefore, the composition of the membrane in concert with proteins that influence the compartmentalization of the plasma membrane or contribute to delineate intracellular signaling molecules are key in controlling leukocyte navigation. This becomes evident by the fact that mislocalization of membrane proteins is known to deliriously affect cellular functions that may cause diseases. In this review we summarize recent advances made in the understanding of how membrane cholesterol levels modulate chemokine receptor signaling and hence leukocyte trafficking. Moreover, we provide an overview on the role of membrane scaffold proteins, particularly tetraspanins, flotillins/reggies, and caveolins in controlling leukocyte migration both in vitro and in vivo.